2010
DOI: 10.1007/978-3-642-13754-9_15
|View full text |Cite
|
Sign up to set email alerts
|

What Is in a Step: New Perspectives on a Classical Question

Abstract: Abstract. In their seminal 1991 paper "What is in a Step: On the Semantics of Statecharts", Pnueli and Shalev showed how, in the presence of global consistency and while observing causality, the synchronous language Statecharts can be given coinciding operational and declarative step semantics. Over the past decade, this semantics has been supplemented with order-theoretic, denotational, axiomatic and game-theoretic characterisations, thus revealing itself as a rather canonical interpretation of the synchrony … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…Proving the soundness of causality analyses necessarily requires maintaining some form of refinement ("constructiveness" or "dependency") information about a lower-level asynchronous micro-step semantics. The first to observe this were Huizing et al [43] who showed that combining compositionality, causality and the Synchrony Hypothesis cannot be done within a single-levelled semantics (see also [24]). In other words, causality analysis establishes consistency of a synchronous macro-step with respect to an asynchronous micro-step execution model.…”
Section: Motivationmentioning
confidence: 93%
“…Proving the soundness of causality analyses necessarily requires maintaining some form of refinement ("constructiveness" or "dependency") information about a lower-level asynchronous micro-step semantics. The first to observe this were Huizing et al [43] who showed that combining compositionality, causality and the Synchrony Hypothesis cannot be done within a single-levelled semantics (see also [24]). In other words, causality analysis establishes consistency of a synchronous macro-step with respect to an asynchronous micro-step execution model.…”
Section: Motivationmentioning
confidence: 93%
“…Various other approaches with their own admissible scheduling schemes have been considered for statecharts. The three most prominent approaches are due to Pnueli and Shalev [24,12], Boussinot [7] and Berry and Shiple [29,5]. None of them considers sequential control flow as SC does.…”
Section: Related Workmentioning
confidence: 99%